Microstructure evolution and shear strength of full Cu3Sn- microporous copper composite joint by thermo-compression bonding. Issue 5 (14th May 2021) - Sun, F; Pan, Zhen; Liu, Yang; Li, Xiang; Liu, Haoyu; Li, Wenpeng
Abstract : Purpose: The purpose of this paper is to quickly manufacture full Cu3 Sn-microporous copper composite joints for high-temperature power electronics applications and study the microstructure evolution and the shear strength of Cu3 Sn at different bonding times. Design/methodology/approach: In this paper, a novel structure of Cu/composite solder sheet/Cu was designed. The composite solder sheet was made of microporous copper filled with Sn. The composite joint was bonded by thermo-compression bonding under pressure of 0.6 MPa at 300°C. The microstructure evolution and the growth behavior of Cu3 Sn at different bonding times were observed by electron microscope and metallographic microscope. The shear strength of the joint was measured by shear machine. Findings: At initial bonding stage the copper atoms in the substrate and the copper atoms in the microporous copper dissolved into the liquid Sn. Then the scallop-liked Cu6 Sn5 phases formed at the interface of liquid Sn/microporous copper and liquid Sn/Cu substrates. During the liquid Sn changing to Cu6 Sn5 phases, Cu3 Sn phases formed and grew at the interface of Cu6 Sn5 /Cu substrates and Cu6 Sn5 /microporous copper. After that the Cu3 Sn phases continued to grow and the Cu3 Sn-microporous copper composite joint with a thickness of 100 µm was successfully obtained. The growth rule of Cu3 Sn was parabolic growth. The shear strength of the composite joints was about 155 MPa. Originality/value: This paper presents a novel full Cu3 Sn-microporous copper composite joint with high shear strength for high-temperature applications based on transient liquid phase bonding. The microstructure evolution and the growth behavior of Cu3 Sn in the composite joints were studied. The shear strength and the fracture mechanism of the composite joints were studied.